STUDY ON THE EFFECT OF ENZYME TREATMENT CONDITIONS ON EXTRACTION EFFICIENCY AND MACADAMIA (Macadamia integrifolia) OIL QUALITY (Vietnam Journal of Agriculture and Environment, 2023)
Macadamia nut oil is a source of healthy edible oils with a high content of unsaturated fatty acids and rich in bioactive compounds. Recent research has focused on developing new methods for extracting oil from macadamia nuts to enhance quality and improve oil extraction efficiency. In this study, we evaluated the enzyme treatment conditions to obtain higher oil yield and better oil quality from macadamia nuts. Specifically, we analyzed oils yield (%), peroxide value, acid and iodine value, saponification value, fatty acid composition, and sensory evaluation. The results showed that,among three enzymes tested (Viscozyme® L, Pectinex® Ultra SPL, Celluclast® 1.5L), Viscozyme® L was selected due to its superior oil extraction efficiency. Viscozyme® L enzyme demonstrated higheffectiveness when the particle fragment size was< 2 mm, combined with a treatment concentration of 0.5%, a treatment duration of 2 hours, and the addition of water at a rate of 30% (v/w — volume compared to weight of macadamia nut). Under these optimized conditions, the oil yield reached approximately 65 to 66%, a significant improvement compared to other treatment conditions yielding only about 15 to 20%. Furthermore, the acid and peroxide values were lower, and the oil exhibited favorable sensory characteristics. Notably, the fatty acid composition of the oil remainedunaffected by the enzymatic treatment. Consequently, this enzyme treatment method can be employed before pressing to increase the oil extraction yield and enhance the oil’s quality, making it suitable for development and application in the functional food, cosmetic, and pharmaceutical industries.